(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
This paper focuses on a particular factor of Latinization (the constant and intense interaction between Romano-Italic immigrants and local communities) in order to highlight the potential of epigraphic and numismatic sources produced by single cities instead of approaching this process from a more generalist point of view covering wider territories. Some case studies from the Eastern and Southern areas have been selected with this aim: Ampurias, Tarragona, Castulo and Sagunto.